2004
DOI: 10.1149/1.1736682
|View full text |Cite
|
Sign up to set email alerts
|

Chromate Conversion Coating on Aluminum Alloys

Abstract: By means of the combined use of scanning electron microscopy, energy dispersive spectroscopy, and atomic force microscopy in the Kelvin probe mode the mechanism of the chromate conversion coating ͑CCC͒ formation, discussed in the first part of the paper, was extended to the case of AA2024, taking into account the effect of the intermetallics ͑IMCs͒. It was found that the cathodic IMCs play a fundamental role during the nucleation of the CCC, since they act as preferential nucleation sites. Besides, the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 42 publications
5
23
0
Order By: Relevance
“…18,21,22 McGovern et al 21 concluded that the deposition rate on Mg-containing intermetallics slowed with increased Cu content due to adsorption of cyanide on the Cu-rich sites. The cyanide is derived from potassium ferricyanide that is added to commercial CCC bath formulations to accelerate the coating deposition process on aluminum.…”
Section: Resultsmentioning
confidence: 99%
“…18,21,22 McGovern et al 21 concluded that the deposition rate on Mg-containing intermetallics slowed with increased Cu content due to adsorption of cyanide on the Cu-rich sites. The cyanide is derived from potassium ferricyanide that is added to commercial CCC bath formulations to accelerate the coating deposition process on aluminum.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the formation of a Cr 3+ monolayer inhibits oxygen and further Cr 6+ reduction [18,[27][28][29][30][31][32]. Debate still exists regarding the control over the anodic dissolution of active phases [33].…”
Section: Introductionmentioning
confidence: 99%
“…This result indicated that a chemical reaction occurs on the aluminum alloy, leading to the formation of a surface newly created by the chromate solution. This film formation may be adjusted depending on temperature, pH condition, coating time, and chromate solution concentration, [24][25][26][27] which the effects will be contributed in further research. Fig.…”
Section: Surface Characterization Of Conversion Coatingsmentioning
confidence: 99%
“…During the oxidation process, pH of the solution could be increased as forming the chromate film. 17,18) Hence, the coating solution must contain an oxidizing agent; oxidizing agents constitute various forms of acid, where it simultaneously functions as a pH control agent. Accordingly, for effective film formation, the processing time of the chromate solution, as well as pH and temperature, should be appropriately set to form a waterinsoluble salt.…”
Section: Introductionmentioning
confidence: 99%